Flow Structure within an Aggressive S-Shaped Intermediate Compressor Duct. Issue 1 (May 2021) - Kasper, Aaron; Hergt, Alexander; Stürzebecher, Thomas; Grund, Sebastian; Flamm, Jasmin; Nicke, Eberhard
Abstract: As part of Clean Sky 2 (Engines ITD), a working group, formed by the DLR Institute of Propulsion Technology, MTU Aero Engines and GKN Aerospace, is setting up a complete compression system module (LPC/ICD/HPC). The aim of the project is to shorten the intermediate compressor duct (ICD), which connects the low pressure compressor (LPC) and high pressure compressor (HPC). This leads to a reduction of the axial length and weight of the overall engine and thus a reduction of the specific fuel consumption. In order to identify measurement-technologies and mitigate risks for this experimental set-up, a non-rotating testrig was set up in advance to investigate two different test vehicles. In a first step an ICD demonstrator was set up, which had a reduced axial length of 25%, compared to currently operating designs. This design predicted no separation or performance losses inside of the aggressive s-shaped contour. In a second step another demonstrator was installed with an even shorter axial length of 50% axial length reduction, compared to todays state of the art configurations. In this demonstrator the design was chosen to exceed the functional limit according to today's CFD prediction and thus explore the potential for further length reduction in the future and to create a data base for numerical tool validation. The two configurations were tested at DLR Cologne. The test channel offers the possibility to use a variety of different measurement techniques to determine the flow behavior inside the ICD. This paper presents the oil streak pattern taken on the hub area between the struts and the ones taken on the pressure and suction side of the outlet guide vanes (OGV- LPC) for both demonstrators.